Propranolol-induced gingival hyperplasia with Nager syndrome: A rare adverse drug reaction - Syed Ahamed Raheel; Omar Bashar Kujan; Bassel Tarakji; Dilshad Umar; Salah Ibrahim (Wolters Kluwer Medknow Publications, 2016)
Drug reactions are a group of reactionary lesions generally show their manifestations in the oral cavity. The drug reactions may vary from local rashes to well-developed swellings in the oral cavity especially involving the gingiva. Most of the drug reactions are asymptomatic and commonly triggered from the active metabolite of a drug used for a long time. Nager syndrome is a group of acrofacial dysostosis that usually results in craniofacial and limb malformations. The craniofacial defects are very similar to the mandibulofacial dysostosis. A very early intervention is needed for the habilitation of the patient especially when it is concerned with speech and language development. This paper reports a case of a 32-year-old female with craniofacial, limb, and skeletal abnormalities along with a drug-induced gingival hyperplasia.